2020
DOI: 10.2147/dmso.s266901
|View full text |Cite
|
Sign up to set email alerts
|

<p>Empagliflozin in Type 2 Diabetes Mellitus Patients with High Cardiovascular Risk: A Model-Based Cost-Utility Analysis in China</p>

Abstract: Purpose: To evaluate the cost-utility of empagliflozin, in addition to best available standard care (BASC), for the treatment of adult patients with T2DM at high cardiovascular risk from the Chinese healthcare system perspective. Methods: A Microsoft Excel-based patient-level simulation model, based on the EMPA-REG OUTCOME trial data, was adapted and used to project individual's clinical and economic outcomes over a lifetime horizon. The cost and utility values were derived from databases and published studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In addition, given the recent increase in diabetes incidence at a younger age due to lifestyle changes, 114 the actual earnings and expenses affected by the reduction or cessation of work productivity should also be evaluated. In parallel with several successful RCT results showing a risk reduction of cardiovascular and renal events with SGLT2i in patients with T2DM, several studies using a simulation model suggested better cost‐effectiveness of SGLT2i compared to that of non‐SGLT2i treatment when used in addition to the standard of care 115–121 . Moreover, an observational study using a database in the US and Sweden demonstrated lower healthcare costs of SGLT2i initiation compared to those of DPP4‐i or other non‐SGLT2i treatments 122,123 .…”
Section: Recent Diabetes Studies In Japanmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, given the recent increase in diabetes incidence at a younger age due to lifestyle changes, 114 the actual earnings and expenses affected by the reduction or cessation of work productivity should also be evaluated. In parallel with several successful RCT results showing a risk reduction of cardiovascular and renal events with SGLT2i in patients with T2DM, several studies using a simulation model suggested better cost‐effectiveness of SGLT2i compared to that of non‐SGLT2i treatment when used in addition to the standard of care 115–121 . Moreover, an observational study using a database in the US and Sweden demonstrated lower healthcare costs of SGLT2i initiation compared to those of DPP4‐i or other non‐SGLT2i treatments 122,123 .…”
Section: Recent Diabetes Studies In Japanmentioning
confidence: 85%
“…In parallel with several successful RCT results showing a risk reduction of cardiovascular and renal events with SGLT2i in patients with T2DM, several studies using a simulation model suggested better cost-effectiveness of SGLT2i compared to that of non-SGLT2i treatment when used in addition to the standard of care. [115][116][117][118][119][120][121] Moreover, an observational study using a database in the US and Sweden demonstrated lower healthcare costs of SGLT2i initiation compared to those of DPP4-i or other non-SGLT2i treatments. 122,123 Although the Japanese database has the strength of detailed information regarding cost, healthcare cost-related studies remain limited, including indirect cost analysis and the quality-adjusted life years.…”
Section: Diabetes-related Healthcare Costsmentioning
confidence: 99%
“…Hospitalization was found to be one of the two largest contributors to direct costs of type 2 diabetes in economically developed countries 31 , which supports similar findings from the American Diabetes Association 3 . Cost-effectiveness modeling analyses suggest that empagliflozin is a highly cost-effective treatment in Japan 32 and China 33,34 . Given the economic burden of type 2 diabetes, the impact of empagliflozin on medical costs in routine clinical care will be analyzed for individual countries in the EMPRISE East Asia study.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study evaluating the cost-effectiveness of empagliflozin versus standard of care in adult patients with T2D and high risk of CVD in Chinese population was identified in the public domain [ 18 ]. This study was conducted using a patient level simulation model developed in MS Excel, based on the EMPA-REG OUTCOME trial data, and assessed rates of outcome, events, costs, LYs, QALYs, and ICER.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese FDA). However, due to the relatively higher prices compared to other conventional oral antidiabetic drugs, treatment with empagliflozin may impose a potential economic impact on the healthcare payer [ 18 ]. Despite the rapid increase in the prevalence and economic burden of diabetes in China, Mao and colleagues have highlighted that a national strategy or special financing mechanism to meet these challenges is lacking in China [ 19 ].…”
Section: Introductionmentioning
confidence: 99%